Questioning the Islam of Abu Thalib: Critical Study to the Sunni’s Hadith and the Shiite’s Hadith - Achmad Darojat Jumadil Kubro; Nyarminingsih Nyarminingsih; Isti Faizah (Millati: Journal of Islamic Studies and Humanities, 2019)
Sunnis and Shiites place the Hadith as a source of law, but both have different methods of examining Hadith.  The most prominent difference is how both of them accept the Prophet companions as a hadith narrator. Sunnis believe that all companions were just. But this examination was rejected by the Shiites. The second difference is the reception about the ma’sum. Sunnis reject the concept of ma'sum other than the Prophet, while Shiites believe imams of ahlu al-bait are ma’sum. The implication of these differences is the different narratives of Islamic history, which are based on the hadith. In this issue is the case of the Islam of Abu Thalibwhich is narrated from each different tradition. Therefore, this research is trying to examine the validity of their narrations and its historicity. The result of this paper is that al-Musayyab bin Hazn, the Prophet companion who narrate the hadith about the death of Abu Thalib, is judged differently by each traditions. Sunnis judged him with Siqah, while Shiites said that he only became Islam after fathu makkah and he was not at the scene when Abu Thalib died.